Circumferential skin defect - Ilizarov technique in plastic surgery - Madhuri, Vrisha; Kurpad, R Shankar; Nithyananth, Manasseh; Jepegnanam, S Thilak; Titus, V. T.K.; Dhanraj, Prema (Indian Journal of Plastic Surgery, 2004)
A young man had an open fracture of the tibia with bone and soft tissue loss in the distal part of the left leg following a crush injury. The circumferential skin defect was successfully treated with controlled lengthening of the distal skin by the Ilizarov technique using nylon wires and skin staples to apply traction. This was combined with limb reconstruction done simultaneously using orthofix external fixator. This case report highlights the use of an orthopaedic technique to provide skin cover in distal leg.
Keywords: Circumferential skin loss; Ilizarov technique; distal leg soft tissue loss; skin elongation; open fracture tibia